Routing strategy in disconnected mobile ad hoc networks with group mobility - Chong, Peter Han Joo (2013)
Most of the current proposed routing protocols in delay-tolerant network (DTN) are designed based on the entity mobility. In this article, we consider the routing in DTN with group mobility, which is useful in modeling those cooperative activities. The new proposed routing scheme is called group-epidemic routing (G-ER). G-ER is designed on the basis of one DTN protocol called epidemic routing (ER). In G-ER, two strategies related to the unique characteristics of the group mobility have been proposed to greatly improve ER. The first is to treat each group as a single node and exchange packets between groups instead of individual nodes. Thus, the resource-consuming problem of ER could be much alleviated. In the meantime, exchanging packets between two groups could speed up the packet delivery. The second is the buffer sharing inside a group, which is supported by the cooperative nature in group mobility. Moreover, we specifically propose a group dynamic model for group mobility to realize group splitting and merging. The performance of G-ER is studied by extensive simulations and compared with ER and dynamic source routing (DSR). Results show that G-ER outperforms ER and DSR in different network scenarios even with group dynamics.